Evaluation of AFM Probes and Instruments with Dynamic Cantilever Calibrator. (30th January 2018) - Alexander, John; Belikov, Sergey; Magonov, Sergei; Smith, Mark
ABSTRACT: The main functions of the dynamic cantilever calibrator (DCC), which are related to characterization of AFM probes and instruments, are demonstrated on a variety of probes. The resonant frequency, Q-factor and spring constant of the rectangular and V-shaped probes were evaluated by thermal tune method. The inverse optical sensitivity and optical beam deflection noise, which define performance of AFM microscopes, were extracted from DCC data. Peculiarities of thermal tune studies and the use of DCC for advanced applications are discussed.